DEVELOPMENT OF EARLY WARNING SYSTEM SITU GINTUNG AT FLOOD PERIOD - Muhammad Sidik Permana; Idham Riyando Moe (Universitas Lambung Mangkurat, 2014)
Situ Gintung disaster that occurred on March 27, 2009 had caused a lot of losses. Thus, flood control as one of the mitigation to be important in order to manage flooding in the catchment upstream at Situ Gintung. Disaster-prone areas is Cirendeu Village, and Ciputat Timur. Lack of hydrological information which often leads to uncertainty inflow in Situ Gintung catchment area, so the integration system between real-time hydrological information to be runoff model needs to be developed.Simulation development starts with giving input in real-time rainfall data generated from Automatic Rainfall Recorced at Situ Gintung (x: -6.30023, y: 106.76424). Data was sent by hydrological's station attendant to server room using Short Message Service (SMS). Furthermore, data that was received will be simulated by system directly to get flood forecasting calculation based on the catchment area of Gintung.The results of these simulations provide time information (t) and peak discharge (Q) inflow flood hydrograph directly and earlier. Integration between Automatic Rainfall Recorced at Situ Gintung and Rainfall-Runoff model using HEC-HMS can provide flood hydrograph early. So that the peak water discharge and water level information can be informed earlier and as a tools for the local government for the next flood events prior to take decision earlier. Keywords: Situ Gintung, realtime, Automatic Rainfall Recorced, Rainfall-Runoff model, HEC-HMS.